Flight Control System Design and Dynamic Simulation for DJI F450 Quadcopter UAV using Pole Placement Tuning Method - Jemsa, Annis Syahirah; Shamsudin, Syariful Syafiq; Pairan, Mohammad Fahmi (Progress in Aerospace and Aviation Technology, 2024)
This paper presents the flight control design of a quadcopter-based unmanned aerial vehicle using an improved PID tuning method based on pole placement (PP) to achieve the desired time response specification. The flight of a quadcopter UAV presents a difficult control problem because it is a fast-responsive and unstable nonlinear system. This study employed the X-Plane flight simulator to assess the control gain values of the autopilot system. The autopilot system was developed using the PID controller in the LabVIEW environment, utilizing the Software in the Loop (SIL) approach. A series of simulated flight experiments were carried out to verify the performance of the proposed controllers and assess the effectiveness of the control systems. The findings suggest that PID controllers, when tuned using the pole placement (PP) technique, can achieve satisfactory position tracking performance during hovering movements, with x and y positions staying within ±0.5 m limits. The controller demonstrated sufficient resilience in handling wind turbulence of 4.5 m/s during a circular path tracking simulation. It achieved position errors of 0.1306 m, 0.0832 m, and 0.2881 m in the x, y, and z positions, respectively, while maintaining a heading error accuracy of less than 3º as per the intended specification.